The place of peripheral rural areas in the construction, by and for tourism, of the identity of the region of Dalat (Vietnam) - Truong Thi Lan Huong; Pierre Dérioz (Via@)
The objective of this article is to understand the place that peripheral spaces and landscapes hold in matters of tourism development, both in the tourist offer and in the construction of the local identity of a region where main center attractor is the city of Dalat, a recognized tourist destination in the Highlands of Vietnam. This study analyzes the way in which the components of these spaces (physical elements, activities and image) contribute to the identity of the Dalat region, based on the in-situ study, official documents, photographs, maps and semi-structured interviews with different local stakeholders. The results show that peripheral spaces have occupied and still occupy an important place in the tourist development of the city and in its image as a destination. But there is for the moment no or very few interactions between these peripheral zones, of which absolute dependence on the center restricts their dynamism and their possibilities of opening.